Unveiling localized electronic properties of ReS2 thin layers at nanoscale using Kelvin force probe microscopy combined with tip-enhanced Raman spectroscopy - Luo, Yu; Su, Weitao; Zhang, Juanjuan; Chen, Fei; Wu, Ke; Zeng, Yijie; Lu, Hongwei (Chinese physics B, 2023)
Electronic properties of two-dimensional(2D)materials can be strongly modulated by localized strain.The typical spatial resolution of conventional Kelvin probe force microscopy(KPFM)is usually limited in a few hundreds of nanome-ters,and it is difficult to characterize localized electronic properties of 2D materials at nanoscales.Herein,tip-enhanced Raman spectroscopy(TERS)is proposed to combine with KPFM to break this restriction.TERS scan is conducted on ReS2 bubbles deposited on a rough Au thin film to obtain strain distribution by using the Raman peak shift.The localized contact potential difference(CPD)is inversely calculated with a higher spatial resolution by using strain measured by TERS and CPD-strain working curve obtained using conventional KPFM and atomic force microscopy.This method enhances the spatial resolution of CPD measurements and can be potentially used to characterize localized electronic properties of 2D materials.